Vaccination with a Replication-Dead Murine Gammaherpesvirus Lacking Viral Pathogenesis Genes Inhibits WT Virus Infection - Dipanwita Mitra; Darby G. Oldenburg; J. Craig Forrest; Laurie T. Krug (Viruses)
Gammaherpesviruses are oncogenic pathogens that establish lifelong infections. There are no FDA-approved vaccines against Epstein–Barr virus or Kaposi sarcoma herpesvirus. Murine gammaherpesvirus-68 (MHV68) infection of mice provides a system for investigating gammaherpesvirus pathogenesis and testing vaccine strategies. Prime-boost vaccination with a replication-dead virus (RDV) that does not express the essential replication and transactivator protein (RTA) encoded by ORF50 (RDV-50.stop) protected against WT virus replication and reduced latency in C57BL/6 mice, and prevented lethal disease in Ifnar1−/− mice. To further improve the RDV vaccine and more closely model KSHV vaccine design, we generated an RDV lacking the unique M1-M4 genes and the non-coding tRNA-miRNA-encoded RNAs (TMERs) 6, 7, and 8 that collectively promote latency of MHV68 in vivo. Prime-boost vaccination of mice with RDV-50.stop∆M1-M4 elicited neutralizing antibodies and virus-specific CD8 T-cell responses in the lungs and spleens, the respective sites of acute replication and latency, that were comparable to RDV-50.stop vaccination. When challenged with WT MHV68, vaccinated mice exhibited a near-complete block of lytic replication and a reduction in latency and reactivation. We conclude that the unique M1-M4 genes and TMERs 6, 7, and 8, which are major determinants of WT MHV68 pathogenesis, are not required for eliciting protective immunity.